Material recyclability project 3 (durian husk recycling) - Tan, Yee Nern (2019)
After careful study, the author found that current practice of durian recycling is very labor intensive and carries huge risk to the user. Convention methods require manual collection of durian husk from individual fruit vendors. Manual transportation of durian husk requires intensive human labor. One of the first steps in conventional recycling process involved manually chopping up durian husk into smaller pieces. This process is highly labor intensive. Such labor-intensive processes in conventional recycling methods carry high risk of muscular injuries and cause fatigue to user. Furthermore, the entire recycling process takes a lot of time as the processes involved in the durian recycling takes a long time to complete in natural environment. From the above observation, the author has decided to design a durian husk recycling machine to replace human labor. The machine is designed to be highly automated with minimum human input for added convenience to the user. Most importantly, the recycling machine enables humans to leverage on mechanical work to complete the job of recycling durian husk. The report will be bringing us through each individual process involved in the conventional durian husk recycling and explain in great details how the machine is designed to help humans leverage on mechanical power to make the recycling task so much easier for the user.